From Colonial Silences to Republican Publicities: Medicine, Women’s Bodies, and the Modern State in Nora Jaffary’s Reproduction and Its Discontents - Holler, Jacqueline (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2018)
Nora Jaffary’s Reproduction and Its Discontents surveys reproduction in Mexico between 1750 and 1905, proceeding through a systematic reconstruction of varied topics: perceptions of virginity; pregnancy, conception, and birth attendance; contraception and abortion; infanticide; monstrous births; and finally, the emergence of obstetrics and gynecology. Jaffary deftly synthesizes these themes to advance a clear and compelling argument: that in Mexico, scrutiny, surveillance, and control of women’s reproductive bodies increased apace with scientific modernity; and that modernity was marked by a conflation of reproduction with national identity and destiny. This article reviews the work’s contributions and engages with several methodological and historiographical themes: the way in which Jaffary interprets documentary silences and absences; the role of the nineteenth-century church and its apparent withdrawal from public debate on matters of reproduction; and publicity and the agency of the public in shaping new attitudes toward reproduction. Jaffary’s book makes significant contributions to the growing literature on gender, the public sphere, and the state in nineteenth-century Latin America. Reproduction and Its Discontents immeasurably enhances our understanding of modernizing Mexico and contributes to our knowledge of the particularly Latin American tropes of modernity.